Akibat hukum terhadap surat kuasa menjual yang dibuat secara notariil dalam penjatuhan pajak terhutang - Prandika, Muchammad Ekky; Supriyadi, Supriyadi (Jurnal Cakrawala Hukum, 2021)
This article has the intent and purpose to find out the legal consequences arising from the existence of a binding sale and purchase agreement (PPJB) with a power of attorney to sell which is notarized which can result in a tax payable, Customs Duty on Acquisition of Land and Building Rights (BPHTB) and Income Tax Collection ( PPh) On the Transfer of HAT, it is reviewed based on the PDRD Law and Government Regulation of the Republic of Indonesia Number 34 of 2016 concerning Income Tax on Income from the Transfer of Land and/or Building Rights, and the Sale and Purchase Agreement on Land and/or Building and its Amendments. The type of research in this research is normative juridical law research, with the approach used in this research being statutory approval. The Sale and Purchase Binding Agreement (PPJB) is a legal breakthrough made by a Notary to overcome the problems faced in the implementation of the sale and purchase of land rights as previously explained. Legal discoveries made and applied by a Notary regarding the use of a Sale and Purchase Binding Agreement (PPJB) in assisting the implementation of the sale and purchase of land rights or as a preliminary agreement before making a Sale and Purchase Deed so that the existence of PPJB does not mean transferring or transferring a Land Right. How to cite item:Â Prandika, M., & Supriyadi, S. (2021). Akibat hukum terhadap surat kuasa menjual yang dibuat secara notariil dalam penjatuhan pajak terhutang.Â Jurnal Cakrawala Hukum, 12(3), 326-333. doi:https://doi.org/10.26905/idjch.v12i3.5176.